Investigation of Traffic Safety Situation at the Level Crossings in Lithuania - Inesa Gailiene; Kestutis Skerys; Gražina Ciparyte (The Baltic Journal of Road and Bridge Engineering)
Traffic safety assurance is the main task on roads as well as railways. At the level crossings both infrastructures cross each other. Therefore the problem of assuring the traffic safety at the level crossings remains permanently actual and is often researched. Requirements for passing the level crossing are clearly defined in the road traffic rules for the road users and in the railway traffic rules for railway carriers. However, despite all these aspects, a level crossing is the place which causes many problems for the users of both infrastructures. Though a number of deaths at level crossings amount to only 2% of the total number of road deaths, it makes 20430% of the total deaths in railways. In this article the problems are described that occur during the use of the level crossings and are concerning the traffic safety assurance. The ways of increasing the traffic safety assurance are also discussed. This problem is actual because of the scientific research and discussions in various countries of the world. The article considers the traffic safety assurance in the level crossings of the Lithuanian roads and provides the context of the other European Union countries. The essential problems of the future are also provided and discussed. Inspections of the road sections were conducted before and behind the fifteen level crossings according to the description of procedures for inspection on road safety. The article consists of the following parts: analysis of problems at the level crossings, statistical analysis of accidents at level crossings in Lithuania and Europe, investigation results and conclusions.